Evaluation of pesticide toxicity at their field recommended doses to honeybees, Apis cerana and A. mellifera through laboratory, semi-field and field studies. (January 2015) - Stanley, Johnson; Sah, Khushboo; Jain, S.K.; Bhatt, J.C.; Sushil, S.N.
Highlights: Acute, semi-field and field toxicity of pesticides to Apis cerana & A. mellifera studied. Chlorpyripos, dichlorvos, malathion, profenofos, monocrotophos & deltamethrin caused 100% mortality. Acetamiprid and endosulfan were safer to both the bees in filter paper and topical bioassays. In second tier, monocrotophos, thiamethoxam, dichlorvos, profenofos and chlorpyriphos are highly toxic. Acetamiprid and endosulfan did not cause any repellent effect on honey bees in the field trials. Abstract: A series of experiments were carried out to determine the acute toxicity of pesticides in the laboratory, toxicity through spray on flowering plants of mustard (Tier II evaluation) and field on both Apis cerana and A. mellifera bees. The overall mortality of honey bees through topical (direct contact) were found significantly higher than that of indirect filter paper contamination assays. Insecticides viz ., chlorpyriphos, dichlorvos, malathion, profenofos, monocrotophos and deltamethrin when exposed directly or indirectly at their field recommended doses caused very high mortality up to 100% to both the bees at 48 HAT. The insecticides that caused less mortality through filter paper contamination viz., flubendiamide, methyl demeton, imidacloprid and thiamethoxam caused very high morality through direct exposure. Apart from all the fungicides tested, carbendazim, mancozeb, chlorothalonil and propiconazole, insecticides acetamiprid and endosulfan were found safer to both the bees either by direct or indirect exposures. Tier II evaluation by spray of pesticides at their field recommended doses on potted mustard plants showed monocrotophos as the highly toxic insecticide with 100% mortality even with 1 h of exposure followed by thiamethoxam, dichlorvos, profenofos and chlorpyriphos which are not to be recommended for use in pollinator attractive flowering plants. Acetamiprid and endosulfan did not cause any repellent effect on honey bees in the field trials endorse the usage of acetamiprid against sucking pest in flowering plants.